A Study of Elephant Care Condition (Elephas Maximus Sumatranus) at Saree Elephant Conservation Center, Aceh Besar - Azura Novitri; Abdullah Abdullah; Mimie Saputri (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2017)
Information about the condition of the elephants at the Elephant Conservation Center (PKG) Saree, Aceh Besar, related to elephant care that can affect the level of animal welfare. This research aims to identify caregiving conditions of Sumatran Elephant in the PKG Saree, Aceh Besar accordance with the level of animal welfare in the environment of domestication. Study of condition of elephant care using 18 variable that refers to the five principles of animal welfare shoppers. This data is used in applicable data primary and secondary data. Primary data collected through triangulation: participatory observation, structured interviews, and documentation. The data obtained is then compiled using the Likert scale took place applies appropriate answer (score 3), lack of appropriate (score 2), and is not appropriate (score 1). Data analysis techniques using Model Miles and Huberman. The condition of the caregiving Sumatran Elephant (Elephas maximus sumatranus) in PKG Saree, Aceh Besar including appropriate categories (43-54) with the level of prosperity in an environment of domestication with a score is 44